2021
DOI: 10.3389/fonc.2021.622182
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modeling Analysis Reveals Immunologic Signatures Associated With Improved Outcomes in High Grade Serous Ovarian Cancer

Abstract: Epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy worldwide, as patients are typically diagnosed at a late stage and eventually develop chemoresistant disease following front-line platinum-taxane based therapy. Only modest results have been achieved with PD-1 based immunotherapy in ovarian cancer patients, despite the fact that immunological responses are observed in EOC patients. Therefore, the goal of this present study was to identify novel immune response genes and cell subsets sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…reported better responses in patients with higher immunoscores in TCGA and OV.AU datasets, although this was not as striking for TCGA patients ( 30 ). However, our results here are in agreement with several other studies, including one from our own lab, that demonstrated no prognostic significance of TILs alone in pre- and/or post-NACT samples ( 10 , 18 , 23 , 24 ). Reasons for these discrepancies could be related to detection method, examination of localization and specific effector subsets of TILs in different studies, number of samples analyzed, or biological variability in patient cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…reported better responses in patients with higher immunoscores in TCGA and OV.AU datasets, although this was not as striking for TCGA patients ( 30 ). However, our results here are in agreement with several other studies, including one from our own lab, that demonstrated no prognostic significance of TILs alone in pre- and/or post-NACT samples ( 10 , 18 , 23 , 24 ). Reasons for these discrepancies could be related to detection method, examination of localization and specific effector subsets of TILs in different studies, number of samples analyzed, or biological variability in patient cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent publication by James et al, exploring immunological signatures in high-grade serous ovarian cancer, the results generated using the ImmunoPrism platform were correlated with the results from an expanded The Cancer Genome Atlas (TCGA) cohort using traditional RNA-seq differential expression analysis methods. 23 …”
Section: Methodsmentioning
confidence: 99%
“…In a recent publication by James et al, exploring immunological signatures in high-grade serous ovarian cancer, the results generated using the Immu-noPrism platform were correlated with the results from an expanded The Cancer Genome Atlas (TCGA) cohort using traditional RNA-seq differential expression analysis methods. 23 For this study, the potential analytes considered when building the Immunoscore include levels of (1) individual immune cell models (listed above, and reported as a percentage of total cell content of the tissue analyzed), (2) the total immune cell content (listed above, and reported as a percentage of the total cell content of the tissue analyzed), and (3) the expression of immune escape genes (listed above, and reported as transcripts per million, TPM).…”
Section: Rna Extraction and Predictive Immune Modeling Analysismentioning
confidence: 99%
“…[96] Higher LAG-3 expression in tumor tissues is related to an adverse prognosis in most types of cancer, including pancreatic cancer, [97] high-grade soft-tissue sarcoma, [98] salivary gland carcinomas, [99] clear cell renal cell carcinoma, [100] HNSCC, [101] esophageal squamous cell carcino-ma, [52] and oral squamous cell carcinoma. [102] In contrast, higher LAG-3 expression correlates with longer survival in other types of cancer, such as high-grade serous ovarian cancer, [103] blood cancer, [104] esophageal adenocarcinoma, [105] and advanced gastric cancer. [90] Studies on the association of LAG-3 with prognosis in patients with NSCLC, colorectal cancer, and breast cancer have yielded contradictory results.…”
Section: Correlation Between Lag-3 and Efficacy And Prognosis In Cancersmentioning
confidence: 99%